Social economy and human rights - Cárdenas-Rivera, Miguel Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This document aims to articulate the social economy with human rights. It is based on three premises: first, the realization of the right takes as a basis the economy; second, assuming the economy the shape of social economy serves  to carry out the rights (social), and third, the social economy as it wants the realization of human being, based on the principle of humanity, serves to concrete human rights in genere. We begin making clear the space that includes  the social economy and its pursued object. It defines this concept from an  ethical point of view to overcome its ambiguity, due to its usual application in multiple scenarios, situation that leads to taxonomic and meaning confusions. It exposes the real demonstrations which are held in the world economies  with what is known as the «third sector» or «solidarity economy», as well as trends in the economic and political thought that help to make even more  indecipherable the term «social economy» Then it explains the concept in an ethical and collective flat, as a principle that directs social economy to be  assumed as a trend of thought which serves to the realization of human being,  i.e. an individual who exercises fully his rights into society without restriction by the monetary economy to break with the neoclassical model.